AIDATrace : interoperation platform for active monitoring in healthcare environments - Machado, José Manuel (2010)
The introduction of monitoring systems may have a great potential to introduce Ambient Intelligence based monitoring techniques in healthcare environments. On the other hand, current research being sponsored by the European Union presents interoperability issues as a considerable obstacle to implement and fully explore the capabilities of such a technology. Therefore, and in order to contribute to overcome this drawback, in this paper we address the different methodologies put into opera- tion in the healthcare sector, supported by a putative architecture which has been used in different healthcare institutions to suport RFID monitoring systems.